Model Pengujian Gaya Kepemimpinan, Motivasi Kerja melalui Kepuasan Kerja terhadap Kinerja Karyawan Notaris di Pekanbaru - Silvia Sari Sitompul (COSTING : Journal of Economic, Business and Accounting, 2018)
Notary designation for someone who has received legal education licensed by the government to do legal matters, especially as a witness to signing the document. Objects in this study are permanent (active) employees in Notary's office Pekanbaru City. The research population is 894. Sample selection is done using probability sampling method with Simple Random Sampling technique, so that the number of samples taken was 276 employees. In this study, parametric statistics were used with multiple linear regression analysis. The results of this study indicate that leadeship style and satisfaction have significant effect on performance while work motivation has no significant effect on performance. Keywords: Leadership Style, Work Motivation, Job Satisfaction and Employee Performance